The role of telemedicine in acute stroke treatment in times of pandemic. Issue 1 (February 2021) - Hubert, Gordian J.; Corea, Francesco; Schlachetzki, Felix
Abstract : Purpose of review: The coronavirus disease 2019 (COVID-19) pandemic challenges many healthcare systems. This review provides an overview of the advantages of telemedicine during times of pandemic and the changes that have followed the outbreak of the COVID-19 disease. Recent findings: Telemedicine has been utilized during infectious outbreaks for many years. COVID-19 has induced a variety of changes in laws (i.e. data privacy protection) and reimbursement procedures to accelerate new setups of telemedicine. Existing networks provide novel data about teleactivation resulting from social restrictions during the nadir of the lockdown in spring 2020. Summary: Telemedicine is a safe and ideal expert support system for hospitals during infectious outbreaks. It makes high-quality medical procedures possible, limits potentially contagious interhospital transfers, saves critical resources such as protective gear and rescue/emergency transport services, and offers safe home office work for medical specialists.